Communicating health crisis: a content analysis of global media framing of COVID-19 - Jude Nwakpoke Ogbodo; Emmanuel Chike Onwe; Joseph Chukwu; Chinedu Jude Nwasum; Ekwutosi Sanita Nwakpu; Simon Ugochukwu Nwankwo; Samuel Nwamini; Stephen Elem; Nelson Iroabuchi Ogbaeja (Tabriz University of Medical Sciences, 2020)
Background: This study examines the global media framing of coronavirus disease 2019 (COVID-19) to understand the dominant frames and how choice of words compares in the media. Periods of health crisis such as the outbreak of coronavirus pandemic add to the enormous burden of the media in keeping people constantly informed. Extant literature suggests that when a message is released through the media, what matters most is not what is said but how it is said. As such, the media could either mitigate or accentuate the crisis depending on the major frames adopted for the coverage. Methods: The study utilises content analysis. Data were sourced from LexisNexis database and two websites that yielded 6145 items used for the analysis. Nine predetermined frames were used for the coding. Results: Human Interest and fear/scaremongering frames dominated the global media coverage of the pandemic. We align our finding with the constructionist frame perspective which assumes that the media as information processor creates 'interpretative packages' in order to both reflect and add to the 'issue culture' because frames that paradigmatically dominate event coverage also dominate audience response. The language of the coverage of COVID-19 combines gloom, hope, precaution and frustration at varied proportions. Conclusion: We conclude that global media coverage of COVID-19 was high, but the framing lacks coherence and sufficient self-efficacy and this can be associated with media's obsession for breaking news. The preponderance of these frames not only shapes public perception and attitudes towards the pandemic but also risks causing more problems for those with existing health conditions due to fear or panic attack.